Transcending the Philippine Educational Culture through Virtual and Augmented Reality with the Integration of the Learning Management Systems - Mobo, Froilan (Future Science / FSH-PH Publications, 2020)
Amidst the current pandemic situation right now, the Department of Education and the Commission on Higher Education are facing a lot of challenges that will take place this coming opening of classes, and part of their initiative is to adopt the mode of flexible learning. In the case of other Higher Education and other educational sectors which caters to practical and situation cases either scientific or technical ap-proaches in facing the real-time situation. The Researcher is propos-ing a new alternative flexible learning that will ease up the situations of the current pandemic in all education levels, which is the integra-tion of Virtual Reality, of AR learning content as part of the educa-tional authoring tools, a web-based platform for the development of Augmented content, the distribution of which is accomplished through standardized Learning Management Systems (LMS) using SCORM packages library,. Furthermore, a collaborative framework solves the problem of standard integration of Augmented and Virtual Reality applications in education offering a distributed framework which is the Learning Management System platform, (Barbadillo, Barnera, Goñi, & Sánchez, 2014). Upon the implementation of this in-teractive and immersive technology platforms, higher-order thinking or critical thinking skills will develop further.